Real-world implementation and evaluation of a pharmacogenomic clinical decision support system for allopurinol and HLA-B*58:01 - Kuan-Hsuan Chen; Shi-Yun Goh; Chia-Lin Chou; Han-Yi Tsai; Chih-Fang Liu; Chung-Ping Lu; Chin-Chin Ho; Chian-Ying Chou (BMC Medical Informatics and Decision Making, 2026)
Abstract Background Allopurinol-induced severe cutaneous adverse reactions (SCARs), including Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN), are strongly associated with the HLA-B*58:01 allele. Despite guidelines recommending genotyping prior to initiation, clinical implementation remains suboptimal. This study evaluated the real-world effectiveness of an electronic health record (EHR)-integrated clinical decision support system (CDSS) designed to enforce point-of-care HLA-B*58:01 testing. Methods A single-center, retrospective comparative cohort study was conducted at a tertiary referral hospital. We analyzed 1,119 allopurinol-naïve adult patients before (June 2022 to December 2023, n = 483) and after (January 2024 to December 2024, n = 636) CDSS implementation. Effectiveness was assessed via the point-of-care pharmacogenomic (PGx) testing rate, Genotype-Informed Prescribing Adherence Rate (GIPAR), and shifts in prescribing behaviors across specialties. Results Following CDSS implementation, the point-of-care PGx testing rate increased significantly from 6.83% (95% CI: 4.85%–9.47%) to 73.90% (95% CI: 70.32%–77.24%, P < 0.001). Post-CDSS, the system intercepted HLA-B*58:01-positive carriers (8 positive cases identified; 1 blocked directly at CPOE order entry and 7 appropriately withheld), completely preventing hazardous allopurinol exposure (0 positive prescriptions proceeded post-CDSS vs. 5 pre-CDSS, P = 0.003). The overall Genotype-Informed Prescribing Adherence Rate (GIPAR) increased from 7.39% (95% CI: 5.32%–10.12%) to 95.91% (95% CI: 94.08%–97.28%, P < 0.001). Furthermore, Internal Medicine (33.0% to 56.0%, P < 0.001) and Rheumatology (4.0% to 14.0%, P < 0.001) prescriptions increased significantly, whereas Hematology/Oncology orders decreased (50.0% to 19.0%, P < 0.001). Conclusion The implementation of an automated HLA-B*58:01 CDSS successfully bridged the translational gap between PGx guidelines and routine practice, substantially increasing point-of-care testing rates and enforcing genotype-informed prescribing adherence.